Mengamati Kehidupan Kegerejaan Masyarakat Stasiun Tangkiling Dalam Pemahaman Gereja Sebagai Tubuh Mistik Kristus - Brigita Elvaretta; Diyva Grania; Retta Chiara (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
This research was conducted to observe the life of the church at the Tangkiling Station in the light of the Church as the Mystical Body of Christ. People in the Tagkiling Station are less actively involved in church life. Through this study, it is hoped that the people of Tangkiling station will be able to realize the meaning of themselves as the Church of the Mystical Body of Christ which is realized in the life of church. The method used in this research is qualitative method with data collection technique in the form of literature study, observation, front of interview and documentation. The research steps include conservations with informants, informant profiles, theme determination, reflection, implications, syhthesis, prospects or possibilities that will occur. The results show that the people at Tangkiling Stastion have a good church life and it is in accordance with the Church as the Mystical Body of Christ but they do not understand deeply about the meaning of the Church as the Mystical Body of Christ because it has never been given a prior understanding. The inhibiting factors for civic engagement are the lack of people understanding about the meaning of the Church as the Mystical Body of Christ, occupation, transportation and distance and dissent. So the pastoral step that is expected to be able to answer the problem is by conducting continuous catechesis, active involment of pastoral partners anda approaches through visits.